Descriptive Study of Patients With Upper Limb Amputation As Possible Candidates for a Hand Transplant in Medellín, Colombia (2022)
ABSTRACT: Introduction The amputation of the upper limb, especially of the hand, is a serious trauma with significant functional and psychological impact. Treatment options include adaptation to the stump, use of prostheses, and composite tissue transplantation. Unfortunately, in Colombia, to date, there are no epidemiological data that characterize the sociodemographic and clinical variables of patients with upper limb amputation. Objective To describe the clinical and epidemiological characteristics of patients with upper limb amputation in two hospital institutions in the city of Medellín during the period 2018-2019 as a basis for developing a hand transplant program in Colombia. Methods A descriptive cross-sectional study was carried out where a total of 443 medical records were reviewed, of which eight records that met the inclusion criteria were identified. Variables such as age, etiology of amputation, level of amputation, comorbidities, complications, and rehabilitation process were analyzed. The information was collected in the REDCap program, and a descriptive analysis was carried out with the data obtained. Results From a sample of 443 amputee patients, eight were selected that met the inclusion criteria. There were 7/8 men (87%) aged 43 years. A total of 75% came from rural areas. In 3/8 patients, there was amputation of the dominant limb. The most common mechanisms were shear trauma and crushing in the context of an occupational accident. A total of 50% had a complete extra-hospital amputation, and reimplantation was not attempted in any of the cases. The most frequent levels of amputation were the proximal and distal third of the forearm. The longest follow-up time was 12 months. Only two patients mentioned the possibility of using a prosthesis during rehabilitation. Conclusions Three young patients were identified, without comorbidities, with amputation of the dominant limb in the context of an occupational accident and without the possibility of rehabilitation with prostheses who benefit from a possible future hand transplant. However, it is necessary to implement a composite tissue transplantation program and public health policies that allow this procedure to be performed in Colombia